Tuning discrete growth of ultrathin nonstoichiometric Li2−xO2 discs to achieve high cycling performance Li–O2 battery - Wen‐Long Bai; Zhen Zhang; Kai‐Xue Wang; Jie‐Sheng Chen (Battery Energy, 2022)
Abstract Li–O2 batteries (LOBs) with high theoretical energy density are regarded as promising next‐generation energy storage devices. However, the electrochemical performance of LOBs is significantly impacted by the sluggish reaction kinetics of the insulative discharge product, Li2O2. It is envisaged that nonstoichiometric lithium peroxide (Li2−xO2) with an increased charge transfer rate would address this issue. Herein, Ketjen black modified by highly stable polyarylimide was employed as the cathode material for LOBs. As revealed by time‐of‐flight secondary ion mass spectrometry and O K‐edge X‐ray absorption near‐edge structure analyses, nonstoichiometric Li2−xO2, primarily composed of LiO2 and Li2O3, is distributed homogeneously within the discharge products. The formation of nonstoichiometric Li2−xO2 is attributed to the strong interaction of the functional group C═O toward Li ions. In addition, the thickness of the discharge product is well controlled to less than 10 nm, providing a shortened charge transport path and increasing the decomposition kinetics. Consequently, ultrahigh cycle stability (>130 cycles) is achieved with a cutoff capacity of 1000 mAh g−1 at a current density of 400 mA g−1. This study provides a novel strategy for the development of sustainable and durable rechargeable LOBs.